2012
DOI: 10.4236/jdm.2012.24065
|View full text |Cite
|
Sign up to set email alerts
|

Urinary type IV collagen excretion predicts an increased urinary albumin-to-creatinine ratio in normoalbuminuric patients with diabetes

Abstract: Aims: We evaluated whether urinary excretion of type IV collagen (U-COL) may predict an increase in the urinary albumin-to-creatinine ratio (ACR) and what factors regulate U-COL in 145 normoalbuminuric patients with type 2 diabetes. Methods: We measured HbA1c, systolic blood pressure (SBP), urinary 8-hydroxydeoxyguanosine (8-OHdG) and monocyte chemoattractant protein (MCP)-1 at start of this study (Baseline), ACR and U-COL in addition to these measurements at one year later (Evaluation-1), and ACR and SBP afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
1
1
1
Order By: Relevance
“…(12) Ogawa et al in an observational study over a 2-year period also found a significant correlation between the increase of urinary albumin/creatinine ratio to urinary type IV collagen and that in normoalbuminuria subjects, in which type IV collagen levels higher evolved into albuminuria within 2 years. (19) This study found no correlation between HbA1c levels with urinary GGT (Table 3), as well as no significant correlation was found between urinary type IV collagen/ creatinine ratio and hs-CRP with urinary GGT. The role of GGT in this case was not likely occurs through inflammatory mechanisms and accumulation of ECM, to prove which a further study is needed.…”
Section: Discussioncontrasting
confidence: 56%
“…(12) Ogawa et al in an observational study over a 2-year period also found a significant correlation between the increase of urinary albumin/creatinine ratio to urinary type IV collagen and that in normoalbuminuria subjects, in which type IV collagen levels higher evolved into albuminuria within 2 years. (19) This study found no correlation between HbA1c levels with urinary GGT (Table 3), as well as no significant correlation was found between urinary type IV collagen/ creatinine ratio and hs-CRP with urinary GGT. The role of GGT in this case was not likely occurs through inflammatory mechanisms and accumulation of ECM, to prove which a further study is needed.…”
Section: Discussioncontrasting
confidence: 56%
“…A follow-up study showed that 76.8 % of normoalbuminuric type 2 diabetic patients in the high urinary type IV collagen group developed microalbuminuria as opposed to 22.6 % patients in the normal urinary type IV collagen group. This indicated that baseline urinary type IV collagen excretion may be an independent predictive factor for the development of DN in normoalbuminuric type 2 diabetic patients [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…У более чем 2/3 пациентов с СД 2 типа, имеющих нормоальбуминурию и находящихся в группе с повышенной мочевой экскрецией коллагена IV, регистрировалась микроальбуминурия, что позволяет предположить роль базовой экскреции коллагена IV типа в моче как независимого прогнозирующего фактора для развития ДН. В соответствии с официальными рекомендациями комитета по ДН (Diabetic Nephropathy Committee) Японии увеличение уровня коллагена IV типа в моче является одним из ранних диагностических критериев для постановки диагноза ДН [45].…”
unclassified